Mechanisms for doped PEDOT:PSS electrical conductivity improvement - Ahmad Shahrim, Nur'Aishah (Royal Society of Chemistry, 2021)
Due to their good electrical conductivity and versatility, conductive polymers (CPs), in particular poly(3,4- ethylene dioxythiophene) (PEDOT):poly(styrene sulphonate) (PSS) have recently attracted considerable research interests in bioelectronics application. This research aims to provide an insight into the mechanisms in PEDOT:PSS to increase electrical conductivity. As such, the preparation of doped PEDOT:PSS using distinctive approaches such as undergoing treatment and using secondary dopant is focused primarily from the perspective of improving its electrical efficiency. It also systematically addresses various primary parameters, which have a significant effect on its conductivity. Finally, we present the potential of doped PEDOT:PSS for many promising applications, such as bioelectronics, through an in-depth analysis of the most stupendous works recorded from various research groups over the past decade. Therefore, this review is expected to be significantly helpful in promoting more studies as well as covering the way to increased qualification and productivity for future revolutions of organic CP materials